(untitled) (Revista Internacional de Folkcomunicação, 2024)
The present study discusses the role of Folkcommunication as a therapeutic element in health care, as it brings professionals in the field closer to their patients, especially the most vulnerable from a socioeconomic perspective. It is argued that through folkcommunication, the aforementioned reception becomes integral, generating trust, in addition to understanding, essential aspects for adherence to treatment. The work is based on the author’s teaching experiences, combined with case studies, reports and perspectives, in addition to bibliographical research focused on the main theorists of Folkcommunication. These experiences have as their guiding axis the communication laboratory discipline, in which students simulate care in an outpatient environment for patients (who are their own peers) from lower social strata. During this teaching/learning process, students must not only use the medical communication protocols developed by researchers from the universities of Calgary (Canada), Cambridge (United Kingdom), Maastricht (Netherlands), among others, but above all adopt a folkcommunication language, which will result in assertive and humanized guidance for the population in the internship field and in professional practice. Finally, the World Health Organization (WHO) recommends that health is physical, mental and social well-being; In the discussions exposed throughout this paper, it is possible to infer that folkcommunication is a key condition for obtaining this triad. Based on this understanding, a new theoretical field should emerge over years of post-doctoral research: Folkcommunication in Health.